Cerebral hemodynamics and oxygen metabolism in patients with milder and severe forms of sickle cell disease and thalassemia - Liza Afzali‐Hashemi; Koen P. A. Baas; Anouk Schrantee; Erfan Nur; Chau Vu; Soyoung Choi; Silvie Suriany; John C. Wood; Aart J. Nederveen; Bart J. Biemond (HemaSphere)
Abstract Silent cerebral infarcts (SCIs) are present in patients with sickle cell disease (SCD) and thalassemia, but the pathophysiology of SCIs is not fully understood. Previous studies mainly focused on cerebral hemodynamics and oxygen metabolism in patients with severe SCD (HbSS/HbSβ°) but not in milder forms of SCD (HbSC/HbSβ+) and thalassemia despite the high prevalence of SCIs in these patients. In this work, we studied the cerebral hemodynamics and oxygen metabolism, and SCI lesion load in 75 severe and 26 mild adult SCD patients, 18 thalassemia patients (as anemic comparison group), and 30 healthy controls before and after a vasodilatory challenge with acetazolamide. Cerebral blood flow was significantly higher in patients with severe SCD and thalassemia compared to patients with mild SCD and controls (p < 0.05). Conversely, oxygen extraction fraction and cerebral metabolic rate of oxygen (CMRO2) were significantly lower in patients with severe SCD and thalassemia compared to other groups (p < 0.01). In contrast, no difference in SCI volumes was found between mild and severe SCD and thalassemia patients. After acetazolamide administration, oxygen delivery increased less in severe SCD and thalassemia patients compared to other groups (p < 0.01) and CMRO2 decreased only in severe SCD patients (p < 0.01). Given the reduced CMRO2 values in severe SCD and thalassemia patients, we conclude that reduced cerebral oxygen consumption in these patient groups is mostly related to anemia. Our data suggest that the pathophysiology of SCIs in patients with milder forms of SCD might be more related to prior episodes of anemia or other sickle cell‐related factors.